Analisis Yuridis Kepemilikan Ex Tanah Adat Pada Masyarakat Pamboang - Dewi Wulandari; Muhammad Al Habsy Ahmad (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
The aims of this research were to find out the process of acquiring individual rights in the Pamboang community to become individual ownership rights and to understand the handling of obstacles faced in obtaining legal certainty regarding individual ownership rights over customary land in the Pamboang community, Majene Regency. This research was an empirical normative study. The data collection method in this research were primer data and seconder. The result of this research was the process of obtaining rights over customary land and converting it into individual ownership in the Pamboang community, Majene Regency, involves three stages. In order to be recognized as ownership rights over land, it must meet certain requirements or essential elements contained within the concept of ownership itself, such as the elements of hereditary, strongest, and fulfilled, as well as other elements like social function. In order to obtain evidence of ownership rights over land in the form of a land certificate, the land must be registered with the National Land Agency.